Optimizing Abiraterone Delivery through Intratumoral In Situ Implant: A Prospective Pharmaceutical Development Approach (Sciences of Pharmacy, 2023)
Abiraterone acetate is one of the effective therapies in castration-resistant prostate cancer. There is only one dosage form in the form of film-coated tablets. Abiraterone has proven effective but has disadvantages and contraindications that complicate therapy. One of them is a positive food effect affecting the bioavailability and side effects of the drug. Abiraterone is taken strictly on an empty stomach, and the bioavailability of the drug, in this case, reaches only 10%. In addition, the drug is contraindicated in people with hepatic insufficiency since the main metabolism is in the liver. These and other disadvantages can be eliminated by obtaining targeted delivery systems - liposomes and nanocrystals. Another dosage form could be considered for the active pharmaceutical agent that would be cost-effective, accessible and have higher bioavailability for effective treatment. An intratumoral polymeric in situ implant is chosen as an excellent dosage form, the matrix of which will contain an optimized form of abiraterone, which can stably target a tumor.